NO3- selective mini-electrodes as a tool to investigate the NO3- traffic in Chlamydomonas reinhardtii D. - Díaz, Jordi; Rubio-Valverde, Lourdes; Galván, Aurora; Fernández, Emilio; Fernández-García, José Antonio (My University, 2017)
Ion selective NO3- mini-electrodes were used to measure the external NO3- concentration in C. reinhardtii liquid cultures. Electrodes were prepared using glass capillaries (1.5 mm external diameter). Capillaries were cut in 10 cm long pieces, dehydrated for 45 minutes in an oven and silanized by addition of dimethyldichlorosilane in bencene 0.1% (V/V). Once silanized, the capillaries were baked again for 30 minutes. Once cold the capillaries were backfilled with the NO3- ionophore (Fluka: 72549), which contains PVC (5.75% w/w) dissolved in tetrahydrofurane. Then, the NO3- mini-electrodes were stored in dark in a desiccator until tetrahydrofurane gets evaporated. Before use, NO3- selective mini-electrodes were backfilled with 0.1 M NaNO3 and 0.1 M KCl and connected to a high-impedance differential amplifier (WPI FD223). Mini-electrodes were calibrated in N-free Beijerinck medium, which contains 0.1 mM Cl-. In those conditions, electrodes calibration slope was 54 mV/p NO3- in the range 1 - 1000 µM NO3-. The mini-electrodes were used to continuous monitoring of the external NO3- concentration in liquid culture of different C. reinhardtii strains, incubated in N-free Beijerinck medium supplemented with 100 µM NO3Na. Previous to the assays, strains were N starved for 6 days. In the light, wild type strain uptakes NO3- at a rate of 15 nmol NO3-·106 cells-1·h-1, in the dark this rate was one third of this figure. After 5 h, the external NO3- levelled off at 10 µM in the light and around 30 µM in the dark. C. reinhardtii cells cultured in the presence of 2 mM NO3NH4 do not show significant NO3- uptake nor a mutant strain, defective in nitrate transport and having an active nitrate reductase. However, a mutant strain lacking the nitrate reductase shows an enhanced NO3- uptake rate, compared with the value obtained for the wild type in the light.
Keywords: Electrodos selectivos de iones; Microlectrodos; NO3- ion selective; microelectrode; Chlamydomonas